Sustainable tourism development in Muar. - Jamaluddin, Muhammad Sharul Hidayah; Saad, Mazni (2020)
Applying a sustainable tourism concept is important to any tourism destinations. It helps to preserve and conserve the well being of the place which could contribute to the numbers of tourists that went there. Like any other tourism destinations, the participation of tourism stakeholders is the key to ensure its sustainability. A better management of the area should encourage the destination to be more developed in the future. Therefore, this paper aims to identify the factors that affect the sustainable tourism development in Muar and its implications towards the people in general. In such, it is important for tourism stakeholders in the area to conduct programs to attract tourists and manage the destination area. The study was carried out by conducting a survey which targeted around 100 respondents who is living in Muar or anyone that are familiar with it. Descriptive analysis was used to for the study, which focuses on the mean and standard deviation measurement based on the population. It will analyze all four aspects of the questionnaires which are the environmental, social, heritage and economy.